DEFINING STATELESSNESS IN INDIA: JURISPRUDENTIAL ASPECT - et. al., Ruksana Akhtar (International Journal of Modern Agriculture, 2021)
The Final Draft of the National Register of Citizens (NRC) is published for the North-eastern state of India, Assam in 2019. Approximately 1.9 million people are excluded from the said list. So, ‘statelessness’ being a global human rights crisis can be found settling its existence in this matter. However, as a matter of fact, neither the term ‘stateless’ or ‘statelessness’ is defined under the Indian Constitution nor India is a signatory to the UNHCR Conventions creating a vague administration procedure. Therefore, the author of this paper will focus on the jurisprudential aspect of ‘statelessness’ and the background of the phenomenon. Also the relevancy of the subject will be tested by establishing the nexus of the phenomenon. Further, will try to discuss how India can establish the definition of ‘statelessness’ in the jurisprudential aspect under the obligations of international human rights law.